2013
DOI: 10.1177/1753425913488429
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of resveratrol in an MPTP mouse model of Parkinson's-like disease: Possible role of SOCS-1 in reducing pro-inflammatory responses

Abstract: In the present study we used a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson's disease (PD) mouse model to analyze resveratrol neuroprotective effects. The MPTP-induced PD model is characterized by chronic inflammation, oxidative stress and loss of the dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc). We observed that resveratrol treatment significantly reduced glial activation, decreasing the levels of IL-1β, IL-6 and TNF-α, as well as their respective receptors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 55 publications
5
95
0
Order By: Relevance
“…Considering these previous works, we suggest that the observed effects of resveratrol on monoamines could be due to a protective effect on these limiting enzymes (TPH and TH) against oxidizing agents, which could counteract the effect of aging (Rose et al 2014;Wang et al 2011). Similar protective effects of resveratrol on dopaminergic system has been reported against injuries caused by LPS, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), or 6-hydroxyl dopamine (Rose et al 2014;Blanchet et al 2008;Lofrumento et al 2014;Wang et al 2011). Additionally, some works describe an increased TH expression due to resveratrol treatment, pointing out a SIRT1-mediated effect, which, in turn, could also imply histone deacetylation-mediated effects (Chen et al 2007;Kumar et al 2007;Ranney and Petro 2009;Tredici et al 1999).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Considering these previous works, we suggest that the observed effects of resveratrol on monoamines could be due to a protective effect on these limiting enzymes (TPH and TH) against oxidizing agents, which could counteract the effect of aging (Rose et al 2014;Wang et al 2011). Similar protective effects of resveratrol on dopaminergic system has been reported against injuries caused by LPS, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), or 6-hydroxyl dopamine (Rose et al 2014;Blanchet et al 2008;Lofrumento et al 2014;Wang et al 2011). Additionally, some works describe an increased TH expression due to resveratrol treatment, pointing out a SIRT1-mediated effect, which, in turn, could also imply histone deacetylation-mediated effects (Chen et al 2007;Kumar et al 2007;Ranney and Petro 2009;Tredici et al 1999).…”
Section: Discussionmentioning
confidence: 58%
“…Evidences suggest that resveratrol also regulates neuronal function via a SIRT1-dependent mechanism (Araki et al 2004;Baur 2010;Chuang et al 2009), and mechanisms involving monoamine neurotransmission facilitation since resveratrol inhibits monoamine (MAO) catabolism and also monoamine reuptake into presynaptic neurons (Xu et al 2010;Yañez et al 2006). Furthermore, resveratrol protective properties have been reported in neurodegenerative disease models (Li et al 2014;Blanchet et al 2008;Donmez et al 2010;Lofrumento et al 2014;Albani et al 2010;Wang et al 2011) but have not been clearly demonstrated during normal aging (for review, see Baur 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a model of lipopolysaccharide-induced neurotoxicity in midbrain neuron-glia cultures, resveratrol has been reported to protect dopaminergic neurons by reducing microglial reactivity and the generation of ROS and proinflammatory factors (Zhang et al, 2010). Resveratrol also provide neuroprotection in experimental models of PD and diabetes, by diminishing lipid peroxidation and the production of ROS, restoring the levels of antioxidant enzymes, and decreasing the content of proinflammatory cytokines (Ates et al, 2007;Jin et al, 2008;Jing et al, 2013;Khan et al, 2010;Lofrumento et al, 2014;Venturini et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it has been reported that MPTP injections generate activation of microglia and upregulation of proinflammatory cytokines such as TNF-α, IL-1β and IL-6 (Delgado and Ganea, 2003;Lofrumento et al, 2014). Furthermore, in a PD animal model, it has been shown that VIP exerts a neuroprotective effect by blocking inflammation (Delgado and Ganea, 2003), and this anti-inflammatory activity is also observed with PACAP.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…Thus, PACAP38 was used in the in vivo study as the positive control of neuroprotection. In fact, it has been demonstrated by various in vivo studies using for instance mice or rats that PACAP protects dopaminergic neurons against neuroinflammation and neurotoxicity induced by agents such as 6-OHDA and MPTP, and that it restores deregulated motor functions (Brown et al, 2013(Brown et al, , 2014Deguil et al, 2010;Lofrumento et al, 2014;Reglodi et al, 2004bReglodi et al, , 2011Shivers et al, 2014;Wang et al, 2008). Nevertheless, no accounts of in vivo neuroprotective effects with a synthetic PACAP-derived agonist have been reported so far using a PD model.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%